Effects of Dance and Movement Therapy (DMT) versus Progressive Muscle Relaxation(PMR) on Depression among Elderly Residing in Selected Old Age Homes of Haryana: A Quasi Experimental Study - Prakash Jha1 , Srinivasan.P2 , Uma J Deaver3 , Jyoti Sarin4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Depression is a universal health related problem which is increasing the life expectancy worldwide associatedwith morbidity and disability among elderly people. Elderly age group is a controversial issue as it is a naturalprocess which presents a unique challenge for every individual in society. The objectives of the study wereto assess and compare depression among elderly before and after administration of dance and movementtherapy and progressive muscle relaxation, to determine the relationship between depression and to find outthe association of depression with selected variables. Quantitative research approach, quasi experimentalnon equivalent control group pretest post test design was used to collect the data. Sixty participants (30DMT group, 30 PMR group) were enrolled for the study those who fulfilled the inclusion criteria by usingpurposive sampling technique. Homogeneity was checked by enrolling the participants. Data was collectedby using Geriatric Depression Scale (GDS) for assessing depression by interview technique. Analysis wasdone by applying non parametric test after K-S test to check normality of data. Thus findings of the studyshowed effectiveness of dance and movement therapy and progressive muscle relaxation on depression asthe calculated Friedman test Chi square value (DMT ?2 =51.44, p=0.00 and PMR ?2 =52.91, p=0.00) wassignificant at 0.05 in both groups. There was no any significant difference between DMT and PMR groupsin terms of depression. Depression among elderly was found to be statistically significant with duration ofstay in old age homes and history of chronic illness i.e (?=5.764, p=0.05) and (?=49.00, p=0.02) in DMTgroup, and depression among elderly was found to be statistically significant with history of chronic illnessi.e (?=49.00, p=0.04) in PMR group. Conclusion: Dance and movement therapy and Progressive musclerelaxation was effective in reducing depression among elderly as there was significant difference within thegroup.